Chemical constituents from the roots of Myxopyrum smilacifolium - Vuong, Nguyen Quoc; Chien, Vu Van; Hue, Nguyen Thi; Hang, Pham Thi; Hieu, Tran Van; Nhiem, Nguyen Xuan; Cuong, Pham Van (Vietnam Journal of Science and Technology, 2021)
From the roots of Myxopyrum smilacifolium Blume, five known compounds, verbascoside (1), arenarioside (2), myxopyroside (3), 3-formylindole (4), and 5-hydroxymethyl furfural (5) were isolated. Their chemical structures were determined by ESI-MS, 1D, 2D-NMR spectrascopic data analysis as well as in comparison with those reported in the literatures.